Lubricity and tribological properties of dicarboxylic acid and oleyl alcohol based esters - Jumat Salimon,; Waled Abdo Ahmed,; Nadia Salih,; Mohd Ambar Yarmo,; Darfizzi Derawi, (Universiti Kebangsaan Malaysia, 2015)
Synthesis of new lubricants nowadays is increasing to improve the lubricity properties and the quality of lubricant. In the current study, eight diesters with different chemical structures were tested in terms of their suitability as lubricants. The esterification reaction was carried out using Dean-Stark distillation method with some modification. Fourier transformation infra-red (FTIR), proton and carbon nuclear magnetic resonance (1H-NMR and 13C-NMR), were used to verify the chemical structure of the diesters. The results showed that the dioleyl pimelate (DOlP), dioleyl adipate (DOlA), dioleyl glutarate (DOlG), and dioleyl succinate (DOlSuc) showed good low temperature properties with pour point values at -10, -12, -16 and -20°C, respectively. The dioleyl dodecanedioate (DOlD) indicated remarkable flash point value at 305°C and had slightly high oxidative stability temperature (OT) at 183°C. The flash point increased with the number of carbons for dicarboxylic acid used, while oxidative stability was affected by the unsaturated of oleyl alcohol. Tribological study showed that the diesters were non-Newtonian except DOlD, which was Newtonian fluid. All the diesters were found to be boundary lubricants with low coefficients of friction (COF). Overall, the results indicated that all the diesters studied can be used as lubricating base oils.